2022
DOI: 10.1371/journal.pgph.0001016
|View full text |Cite
|
Sign up to set email alerts
|

Estimated prevalence and gender disparity of physical activity among 64,127 in-school adolescents (aged 12–17 years): A multi-country analysis of Global School-based Health Surveys from 23 African countries

Abstract: The Africa sub-region currently lacks quantitative normative data to illustrate the extent of burden and gender inequities of physical activity level in order to inform policy and education, towards meeting the WHO’s 2030 physical activity milestone. The study aimed to provide insights on the current prevalence of sufficient physical activity and gender disparity, using a nationally representative data from the Global School-based student Health Survey (GSHS) from 23 African countries. The study used the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Approximately 25% of boys met the World Health Organization (WHO) recommendation for sufficient physical activity exercise, contrasting with a lower rate of 16% among girls (Ackah et al 2022). This observed sex discrepancy may be attributed to entrenched traditional and religious norms prevalent found in many North African countries.…”
Section: Additional Data Bymentioning
confidence: 97%
See 1 more Smart Citation
“…Approximately 25% of boys met the World Health Organization (WHO) recommendation for sufficient physical activity exercise, contrasting with a lower rate of 16% among girls (Ackah et al 2022). This observed sex discrepancy may be attributed to entrenched traditional and religious norms prevalent found in many North African countries.…”
Section: Additional Data Bymentioning
confidence: 97%
“…The World Health Organization (WHO) physical activity guidelines for adolescents at risk for NCDs recommend accumulating at least an average of 60 minutes of moderate-to-vigorous physical activity (MVPA) per day to attain the most health benefits from physical activity (Saqib et al 2020). According to Ackah et al (2022), a multi-country analysis of Global School-based Health Surveys report that only 20% of adolescents in Africa engage in sufficient physical activity.…”
Section: Additional Data Bymentioning
confidence: 99%
“…Furthermore, only 20% of in-school adolescents met the WHO's recommended PA level, according to a multi-country analysis of Global School-Based Health Surveys from 23 African countries, including Namibia. The Survey also showed that teenage girls in Africa are less active than teenage boys [5].…”
Section: Introductionmentioning
confidence: 99%